2000
DOI: 10.3758/bf03212135
|View full text |Cite
|
Sign up to set email alerts
|

Learning to perceive the relative mass of colliding balls: The effects of ratio scaling and feedback

Abstract: The theory of direct perception holds that competent observers are able to detect optical patterns that specify the relative mass of colliding balls. Heuristic theorists, on the other hand, claim that judgments of relative mass are based on variables that do not specify relative mass. We contrasted these views with an experiment in which participants were given feedback on their ratio-scaled estimates of the relative mass of simulated colliding balls. Correlations between judged relative mass and various kinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
85
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(95 citation statements)
references
References 15 publications
9
85
0
1
Order By: Relevance
“…van der Meer (2000, 2007) showed similar developmental changes in variable use in the control of eye blinking movements during the first 6 months after birth. This process of the education of attention has also been demonstrated in several perceptual tasks: the visual perception of the pulling-force of a stick figure (e.g., Michaels & de Vries, 1998), the visual perception of the relative mass of colliding balls (e.g., Jacobs et al, 2000Jacobs et al, , 2001Runeson et al, 2000;Runeson & Andersson, 2007), and height and length perception by dynamic touch (Menger & Withagen, in press;Michaels et al, 2008;Wagman et al, 2001;Withagen & Michaels, 2005b;Withagen & van Wermeskerken, 2009). 2 These studies all show that the detected variables often correlate with the to-be-perceived property, but are not specific to it.…”
Section: Empirical Studies Of Perception Action Learning and Develmentioning
confidence: 85%
See 2 more Smart Citations
“…van der Meer (2000, 2007) showed similar developmental changes in variable use in the control of eye blinking movements during the first 6 months after birth. This process of the education of attention has also been demonstrated in several perceptual tasks: the visual perception of the pulling-force of a stick figure (e.g., Michaels & de Vries, 1998), the visual perception of the relative mass of colliding balls (e.g., Jacobs et al, 2000Jacobs et al, , 2001Runeson et al, 2000;Runeson & Andersson, 2007), and height and length perception by dynamic touch (Menger & Withagen, in press;Michaels et al, 2008;Wagman et al, 2001;Withagen & Michaels, 2005b;Withagen & van Wermeskerken, 2009). 2 These studies all show that the detected variables often correlate with the to-be-perceived property, but are not specific to it.…”
Section: Empirical Studies Of Perception Action Learning and Develmentioning
confidence: 85%
“…Inclined to an ecological perspective, these studies have searched for specifying patterns in the ambient arrays that uniquely constrain the perception or action. Yet they have revealed that humans often rely on variables that correlate with, but are not specific to, the to-be-perceived property (e.g., Caljouw et al, 2004;Mi-chaels et al, 2001;Tresilian, 1999;van de Langenberg et al, 2006;van der Kamp et al, 1997 However, after feedback they can converge on more useful patterns in the ambient array, but often end up detecting variables that do not specify the to-be-perceived property (e.g., Fajen & Devaney, 2006;Jacobs et al, 2000Jacobs et al, , 2001Kayed & van der Meer, 2000Michaels & de Vries, 1998;Michaels et al, 2008;Runeson et al, 2000;Runeson & Andersson, 2007;van Hof, van der Kamp, & Savelsbergh, 2006, 2008Wagman, Shockley, Riley, & Turvey, 2001;Withagen & Michaels, 2005b;Withagen & van Wermeskerken, 2009). It is beyond the scope of this paper to provide a detailed description of all these studies.…”
Section: Empirical Studies Of Perception Action Learning and Develmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a learning process has been demonstrated, for instance, in the visual perception of pulling force (Michaels & de Vries, 1998;cf. Jacobs, Michaels, Zaal, & Runeson, 2001), the distance and size of freely falling balls , and the relative mass of colliding balls (Jacobs, Michaels, & Runeson, 2000;Runeson, Juslin, & Olsson, 2000). In all these studies, observers differed from one another and changed in the optical variables they used.…”
mentioning
confidence: 99%
“…This raises the issue of interindividual differences in the capacity for perceptual learning. Over the last decade, several ecologically motivated studies have reported considerable individual differences in perceptual learning in Western participants (e.g., Jacobs, Michaels, & Runeson, 2000;Jacobs et al, 2001;Menger & Withagen, 2009;Michaels & de Vries, 1998;Runeson & Andersson, 2007;Withagen & van Wermeskerken, 2009). Participants have been found to vary in the degrees to which they were able to take advantage of feedback in order to attune to more useful informational variables (Withagen & van Wermeskerken, 2009).…”
mentioning
confidence: 99%